Adaptive Synthesis of Functional Amphiphilic Dendrons as a Novel Approach to Artificial Supramolecular Objects - Edr, Antonín; Wrobel, Dominika; Krupková, Alena; Šťastná, Lucie Červenková; Cuřínová, Petra; Novák, Aleš; Malý, Jan; Kalasová, Jitka; Malý, Jan; Malý, Marek; Strašák, Tomáš (International journal of molecular sciences, 2022)
Supramolecular structures, such as micelles, liposomes, polymerosomes or dendrimerosomes, are widely studied and used as drug delivery systems. The behavior of amphiphilic building blocks strongly depends on their spatial distribution and shape of polar and nonpolar component. This report is focused on the development of new versatile synthetic protocols for amphiphilic carbosilane dendrons (amp-CS-DDNs) capable of self-assembly to regular micelles and other supramolecular objects. The presented strategy enables the fine modification of amphiphilic structure in several ways and also enables the facile connection of a desired functionality. DLS experiments demonstrated correlations between structural parameters of amp-CS-DDNs and the size of formed nanoparticles. For detailed information about the organization and spatial distribution of amp-CS-DDNs assemblies, computer simulation models were studied by using molecular dynamics in explicit water.
Keywords: micely; Nanoparticles; Anthracenes; Hydrophobic and Hydrophilic Interactions; Computer Simulation; micelles; zeta potential; silany; computer modeling; Micelles; molecular dynamics; anthraceny; DLS; počítačová simulace; dendrons; voda; nanočástice; Silanes; carbosilane; Water; amphiphiles; hydrofobní a hydrofilní interakce